Preparation method of flexible transparent conductive electrode based on copper-silver composite nanotube shell
By adopting copper-silver composite nanotube shell structure and benzoic acid modified polymethyl methacrylate substrate, the shortcomings in the quality factor, stability and preparation cost of existing metal nanowire electrodes are solved, and a high-performance, low-cost flexible transparent conductive electrode is prepared.
Patent Information
- Application Number
- CN202411926636.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-25
Smart Images

Figure CN119560233A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell, belonging to the technical field of preparing flexible transparent conductive electrodes. Background Art
[0002] Flexible electronic technology is a technology that prepares electronic devices based on organic / inorganic materials on flexible plastic or thin metal substrates. The electronic products prepared by this technology have the advantages of light weight and flexibility, and have broad application prospects in information, energy, national defense and other fields. For example, flexible electronic displays, flexible solar cells, flexible photodetectors, flexible sensors and other products have been put into use in recent years.
[0003] Flexible transparent conductive electrodes are important components of next-generation optoelectronic devices such as flexible solar cells and display screens. Among them, flexible transparent electrodes made of indium tin oxide are widely used due to their good stability, high transmittance and conductivity. However, they have problems such as complex preparation process, poor mechanical stability, expensive raw materials and environmentally unfriendly preparation.
[0004] In order to find alternative materials, other flexible transparent electrodes such as graphene, conductive polymers, carbon nanotubes and metal nanowires are also used to prepare flexible devices. Among them, the graphene electrode has a stable structure, but the preparation cost is high and the electrical properties are unstable. The preparation cost of the conductive polymer electrode is low, but its stability is poor. The carbon nanotube electrode has excellent flexibility, but the square resistance is large and the transmittance is low. The metal nanowire electrode has a mesh structure between the fibers that enhances the optical transmittance, and the multi-path conductive channel makes it have a low square resistance, making it an ideal choice for flexible transparent electrodes.
[0005] However, the current manufacturing process for metal nanowire electrodes still has the following problems and defects: The quality factor of the electrode is low: it is reflected in the low transmittance of the substrate and the poor contact between the nanowires of the electrode, resulting in low conductivity. The low transmittance and conductivity of the electrode will lead to a low quality factor; The electrode has poor stability: after bending, the square resistance will increase significantly. At the same time, there is a problem of poor air stability. After being placed in the air for a period of time, the square resistance will increase significantly. The preparation cost of the electrode is high: it is reflected in the structure of using silver to completely cover the nanowires, which increases the consumption of silver. The materials used for the substrate are expensive, which is not conducive to the commercial production and application of transparent electrodes.
[0006] The above defects and limitations hinder the further application of flexible transparent electrodes, so corresponding improvements are needed in their preparation process. Summary of the invention
[0007] In order to overcome the deficiencies in the prior art, the present invention aims to solve the technical problem of providing a method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell, comprising the following preparation steps: Step 1: dissolving polyvinyl pyrrolidone in deionized water to form a mixture, stirring the mixture in air to form a precursor solution, and the prepared precursor solution can be spun; Step 2: Place the precursor solution into a syringe and a hemispherical droplet appears on the tip of the syringe; Step 3: Set the distance from the spinneret to the square collector, flow rate, and applied voltage range; Step 4: The hemispherical droplets are polarized under high voltage and spun in a square collector to form a nanofiber mesh; Step 5: Put anhydrous ethanol into a culture dish, heat it on a hot plate, place the nanofiber grid on top of the culture dish, and treat the nanofiber grid with anhydrous ethanol vapor to fuse the nodes between the fibers; Step 6: subjecting the nanofiber mesh to thermal evaporation treatment, evaporating metallic silver on the upper surface of the mesh and metallic copper on the lower surface; Step 7: Pre-treat the white glass: ultrasonically clean the white glass with deionized water, acetone, and isopropyl alcohol at room temperature, and then irradiate it with UV to make the white glass hydrophilic; Step 8: Spin deionized water over the pre-treated white glass surface to form a water film; Step 9: The nanofiber grid on the square collector is adhered to the white glass through the action of the water film. During the transfer process, the side of the nanofiber grid coated with metallic silver is adhered to the white glass; Step 10: doping benzoic acid into the polymethyl methacrylate solution to form a mixture, and heating and stirring the mixture to form a benzoic acid-modified polymethyl methacrylate solution; Apply the prepared solution dropwise on the white glass with the metal grid attached, apply it evenly with a scraper, then perform annealing and wait for it to dry; Step 11: Place the dried film in deionized water and let it stand, so that the film automatically falls off the white glass, and finally form a flexible transparent conductive electrode based on the copper-silver composite nanotube shell.
[0009] The concentration of the mixture formed in step 1 is 0.18-0.22 g / ml; Specifically, the mixture is stirred in air for 4-6 hours to form a precursor solution, and the prepared precursor solution can be spun in an air humidity range of 25%-32%.
[0010] In the step 3, the distance from the spinneret to the square collector, the flow rate, and the applied voltage range are set to 10-12 cm, 0.06-0.10 mm / min, and 7.5-8.5 kV, respectively.
[0011] In the step 4, the spinning time in the square collector is 100-130 s, and the coverage is 18%-22%.
[0012] In the step 5, 20-25 ml of anhydrous ethanol is put into a 35 ml culture dish, heated on a hot plate at 50° C., and the nanofiber grid is treated with anhydrous ethanol vapor for 2-3 minutes.
[0013] When the step six is to perform the thermal evaporation treatment, specifically, 50 nm of metallic silver is evaporated on the upper surface of the grid and 50 nm of metallic copper is evaporated on the lower surface, and the evaporation rate is 0.5-0.9 Å / s.
[0014] The step seven specifically involves ultrasonic cleaning the white glass for 15 minutes, followed by UV irradiation for 15 minutes.
[0015] In the step eight, 1-1.5 ml of deionized water is spread on the pretreated white glass surface, and spin coating is performed at a spin coating rate of 1500 rmp and a spin coating time of 30 s.
[0016] The step ten specifically comprises doping benzoic acid with a solid content of 7.5% into a 0.2 g / ml polymethyl methacrylate solution to form a mixture; and heating and stirring the mixture at a temperature of 80° C. and a stirring rate of 3000 rpm for 3 hours to form a benzoic acid-modified polymethyl methacrylate solution.
[0017] The step eleven specifically includes placing the dried film in deionized water and allowing it to stand for 60 seconds.
[0018] The beneficial effects of the present invention over the prior art are as follows: the preparation method provided by the present invention can prepare high-performance flexible transparent electrodes at low cost. On the one hand, the three innovations of using anhydrous ethanol vapor to fuse nanowire nodes, designing a copper-silver composite tube shell structure, and using benzoic acid-modified polymethyl methacrylate as a substrate improve the photoelectric performance and stability of the electrode, and finally prepare a flexible transparent electrode with a square resistance of 2.1Ω· The transmittance is 93%, the quality factor is 0.23, and it is a high-performance flexible transparent electrode that can withstand tens of thousands of bends; on the other hand, a copper-silver composite structure is adopted and polymethyl methacrylate modified with benzoic acid is used as a substrate to reduce the preparation cost while ensuring the high performance of the electrode; the present invention provides an effective solution for the commercial development of flexible transparent electrodes with high stability, high flexibility, high quality factor and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with the accompanying drawings: Figure 1 is a flow chart of the steps of the method for preparing a flexible transparent conductive electrode of the present invention; Figure 2 This is a structural diagram of a flexible transparent conductive electrode based on a copper-silver composite nanotube shell prepared by the present invention; Figure 3 This is a scanning electron microscopic morphology image of a single copper-silver composite nanotube shell of the present invention; Figure 4 This is a scanning electron microscopic morphology image of the electrospun nanofiber mesh before and after being treated with anhydrous ethanol vapor in the present invention; Figure 5 is a scanning electron microscopic morphology image of the flexible transparent conductive electrode of the present invention; Figure 6 is a graph showing the photoelectric performance of the flexible transparent conductive electrode of the present invention; Figure 7 is a mechanical stability relationship diagram of the flexible transparent conductive electrode of the present invention; Figure 8 is a mechanical stability relationship diagram of the flexible transparent conductive electrode of the present invention; Fig. 9 is a graph showing the air stability of the flexible transparent conductive electrode of the present invention; Fig.10 is a relationship diagram of adhesion test of the flexible transparent conductive electrode of the present invention; Fig.11 This is a diagram showing the transformation effect of the polymethyl methacrylate substrate after bending without benzoic acid modification and after benzoic acid modification according to the present invention; Fig.12 It is a test effect diagram of the water contact angle of the present invention. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell. The prepared electrode has a structure similar to a "coaxial cable", wherein the inner core is a PVP nanofiber prepared by an electrostatic spinning process, and the outer shell is a copper-silver composite metal layer formed by depositing a metal silver film and a metal copper film on the upper and lower sides of a PVP nanofiber grid by a vacuum thermal evaporation process, and then the copper-silver composite nanotube shell is embedded in a polymethyl methacrylate film substrate modified by benzoic acid by a substrate transfer method, and finally a transparent electrode with a copper-silver composite nanotube shell structure having high performance, high stability and low cost is prepared.
[0021] The copper-silver composite nanotube shell structure prepared by the present invention combines the advantages of good electrical conductivity of copper and excellent stability of silver, not only taking into account stability and electrical conductivity, but also achieving the purpose of reducing costs; by embedding the copper-plated side in the substrate in the copper-silver composite nanotube shell structure, the problem of easy oxidation of metallic copper can be effectively solved; most of the silver-plated side is also embedded in the substrate, and only a small part is exposed to the air, which can ensure the conductivity of the electrode and reduce the roughness of the electrode surface; when the electrode is bent, the PVP nanowires inside the tube shell structure provide support for the outer metal shell, which can improve the mechanical stability of the electrode and solve the problem of poor toughness of the metal.
[0022] The present invention utilizes anhydrous ethanol vapor to weld grid nodes, and adopts anhydrous ethanol to weld the electrostatically spun nanofiber grid, mainly to fuse the nodes between the fibers, strengthen the connectivity between the nanofibers, and after metal is evaporated on the fiber grid, the conductivity at the fused nodes is better, thereby enhancing the overall conductivity of the electrode; in addition, by using benzoic acid-modified polymethyl methacrylate as a substrate, the substrate preparation cost can be reduced, and the problem of poor mechanical stability of the polymethyl methacrylate substrate can be solved while ensuring excellent optical transmittance.
[0023] The present invention provides a method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell, and the specific preparation steps are as follows: Step 1: Dissolve polyvinyl pyrrolidone (PVP) in deionized water to form a mixture with a concentration of 0.18-0.22 g / ml. Stir the mixture in air for 4-6 hours to form a precursor solution. The solution can be spun at an air humidity range of 25%-32%.
[0024] Step 2: Place 5-10 ml of the precursor solution into a syringe (fixed on a spring pump) and a hemispherical droplet appears on the tip of the syringe.
[0025] Step 3: The distance from the spinneret to the square collector, the flow rate, and the applied voltage range were 10-12 cm, 0.06-0.10 mm / min, and 7.5-8.5 kV, respectively.
[0026] Step 4: The hemispherical droplets will be polarized under high voltage and become Taylor cones. When the electrostatic repulsion is greater than the surface tension, a charged jet will be generated at the bottom of the Taylor cone, usually passing in a nearly straight line, and finally forming a nanofiber grid in a square collector. The spinning time is about 100-130 s, and the coverage is about 18%-22%.
[0027] Step 5: Place 20-25 ml of anhydrous ethanol into a 35 ml culture dish, heat it on a hot plate at 50°C, place the nanofiber grid on top of the culture dish, and treat the grid with anhydrous ethanol vapor for 2-3 minutes to fuse the nodes between the fibers.
[0028] Step 6: The fiber mesh is subjected to thermal evaporation treatment. 50 nm of metallic silver is evaporated on the upper surface of the mesh and 50 nm of metallic copper is evaporated on the lower surface. The evaporation rate is 0.5-0.9 Å / s.
[0029] Step 7: Pre-treat the white glass. At room temperature, ultrasonically clean the white glass with deionized water, acetone and isopropanol for 15 minutes, and then irradiate with UV for 15 minutes to make it hydrophilic.
[0030] Step 8: Spread 1-1.5 ml of deionized water on the pretreated white glass surface, spin-coat at a speed of 1500 rpm and a spin-coating time of 30 s to form a layer of water film.
[0031] Step 9: Adhere the grid on the square collector to the white glass through the water film. During the transfer process, make the side coated with metallic silver adhere to the glass.
[0032] Step 10: Add benzoic acid with a solid content of 7.5% to a 0.2 g / ml polymethyl methacrylate solution to form a mixture. Heat and stir the mixture for 3 hours at a temperature of 80°C and a stirring rate of 3000 rpm to form a polymethyl methacrylate solution modified with benzoic acid. Apply the prepared solution dropwise on the white glass with a metal grid attached, apply it evenly with a scraper, anneal at 50°C, anneal for 5 hours, and wait for drying.
[0033] Step 11: The dried film is placed in deionized water and allowed to stand for 60 seconds. The film will then automatically fall off the white glass, eventually forming a flexible transparent conductive electrode based on a copper-silver composite nanotube shell.
[0034] The flexible transparent conductive electrode prepared by the above process steps has excellent performance and high quality factor. The polymethyl methacrylate substrate modified with benzoic acid has high transmittance; the junction treated with anhydrous ethanol vapor improves the conductivity of the electrode. The transmittance is 93%, the quality factor is as high as 0.23, and the flexible transparent electrode has no obvious change in square resistance after tens of thousands of bendings.
[0035] The flexible transparent conductive electrode prepared by the present invention has good stability, which is reflected in the copper-silver composite nanotube shell structure adopted, which combines the advantages of excellent copper conductivity and high silver stability, while taking into account the light transmittance and conductivity of the electrode while improving the stability. This structure can cleverly embed the copper-plated side in the substrate, leaving only a small part of the silver exposed. The advantage is that the exposed silver is flush with the substrate surface without affecting the conductivity, thereby reducing the roughness of the electrode surface; the copper embedded in the substrate can avoid oxidation caused by contact with air, thereby improving the oxidation resistance of the electrode; the PVP nanofibers inside the copper-silver tube shell can provide a good insulation material for the electrode. The electrode provides a certain supporting force, thereby enhancing the mechanical stability of the tube shell electrode; the polymethyl methacrylate film modified by benzoic acid improves the mechanical stability of the electrode under the premise of having high optical transmittance; the adhesion stability is good, and the square resistance remains basically unchanged after the tape is adhered hundreds of times; the flexible transparent electrode based on the copper-silver composite nanotube shell has strong hydrophobicity and high humidity stability; the preparation cost of the electrode prepared by the present invention is low, which is reflected in the use of a copper-silver composite structure, using copper to replace part of the expensive silver, reducing the consumption of silver, saving costs, and selecting polymethyl methacrylate modified by benzoic acid as a substrate, and the raw material cost of the substrate is low.
[0036] like Figure 1 The flexible transparent conductive electrode preparation process shown in the embodiment of the present invention includes: Electrospun nanofibers are formed into a nanofiber grid on a square collector; metallic silver is evaporated on the upper surface of the nanofiber grid; the grid is turned over and copper is plated on the other surface; a water film is then formed on the surface of white glass by spin coating to impart a certain degree of adhesion; the copper-silver composite nanotube shell is transferred to the white glass under the action of adhesion; a polymethyl methacrylate solution modified by benzoic acid is drop-coated on top of the transferred composite nanotube shell; the drop-coated solution is naturally air-dried to form a thin film; it is soaked in deionized water in order to peel off the polymethyl methacrylate modified by benzoic acid together with the nanotube shell from the white glass, and finally a flexible transparent conductive electrode based on the copper-silver composite nanotube shell is obtained.
[0037] like Figure 2 The figure shows the structure of the flexible transparent conductive electrode based on the copper-silver composite nanotube shell prepared by the present invention. Specifically, the copper-silver composite nanotube shell is embedded in a polymethyl methacrylate substrate, and only part of the silver is exposed to the air to ensure the conductivity of the electrode.
[0038] like Figure 3 Shown is a scanning electron micrograph of a single copper-silver composite nanotube shell, with metallic copper and metallic silver on both sides.
[0039] like Figure 4 The scanning electron micrographs of the electrospun nanofiber mesh before and after treatment with anhydrous ethanol vapor are shown. Figure 4 a is the morphology before anhydrous ethanol vapor treatment. It can be seen that the two nanofibers without vapor treatment have poor connectivity, which will affect the conductivity of the electrode. Figure 4 b is the morphology image after treatment with anhydrous ethanol vapor. It can be seen that the nodes of the two nanofibers are fused together, reducing the overall flatness and also improving the conductivity of the electrode.
[0040] like Figure 5 Shown is a scanning electron micrograph of a flexible transparent conductive electrode based on a copper-silver composite nanotube shell. It can be seen that the composite nanotube shell is completely embedded in the substrate. The substrate can not only provide a certain stress for the shell, but also reduce the roughness of the electrode surface.
[0041] like Figure 6 The photoelectric performance relationship diagram of the flexible transparent conductive electrode is shown, which mainly explores the relationship between coverage and quality factor. It can be seen that when the coverage is about 20%, the square resistance is 2.1 Ω· , the transmittance is 93% and the quality factor is as high as 0.23.
[0042] like Figure 7 Shown is a graph showing the mechanical stability of flexible transparent conductive electrodes, which mainly explores the bending stability of commercial ITO, copper nanotube shell electrode, silver nanotube shell electrode, and copper-silver composite nanotube shell electrode at a bending radius of 5 mm; during the bending process, the mesh structure of the nanotube shell enhances its flexibility; the PVP nanofibers inside the nanotube shell structure provide a certain stress for the outer metal, and the introduction of silver can also improve the mechanical stability of the electrode; after commercial ITO is bent hundreds of times, the square resistance change rate is as high as 375%, and the square resistance change rate of the copper nanotube shell electrode, copper-silver composite nanotube shell electrode, and silver nanotube shell electrode decreases successively during tens of thousands of bendings, but the change rate is within 0.03%, proving that the mechanical stability is good, so the flexibility of the copper-silver composite nanotube shell electrode is better than that of commercial ITO and copper nanotube shell electrode.
[0043] like Figure 8 Shown is a graph showing the mechanical stability of flexible transparent conductive electrodes, which mainly explores the tensile stability of commercial ITO, copper nanotube shell electrodes, silver nanotube shell electrodes, and copper-silver composite nanotube shell electrodes; during the stretching process, the mesh structure can provide a good buffer and enhance its stretchability. The PVP nanofibers inside the nanotube shell structure provide a certain stress for the outer metal. Silver has good flexibility, and the introduction of silver can also improve the mechanical stability of the electrode; therefore, the tensile performance of the copper-silver composite nanotube shell electrode is better than that of commercial ITO and copper nanotube shell electrodes.
[0044] like Fig. 9 Shown is a graph showing the air stability of a flexible transparent conductive electrode, which mainly explores the comparison of the air stability between commercial ITO and copper-silver composite nanotube shell electrodes. Since part of the easily oxidizable metallic copper is embedded in the substrate, preventing direct contact with the air, the copper-silver composite nanotube shell electrode has good air stability. It can be seen from the figure that the two have similar curves, proving that the air stability of the electrode prepared by the present invention can reach the level of commercial ITO.
[0045] like Fig.10 The figure shows the adhesion test relationship diagram of the flexible transparent conductive electrode, which mainly explores the adhesion stability of commercial ITO and copper-silver nanotube shell electrodes. During the adhesion test of the tape, since most of the metal nanotube shells are embedded in the substrate, the metal tube shells are prevented from falling off the substrate. It can be seen that the square resistance change rate does not change much compared with the commercial ITO, which proves that the adhesion stability of the electrode of the present invention can reach the level of commercial ITO.
[0046] like Fig.11 The figure shows the transformation of the polymethyl methacrylate substrate after bending without benzoic acid modification and with benzoic acid modification. Fig.11 a is the substrate that has not been modified with benzoic acid. After thousands of bends, the substrate broke in the middle. Fig.11 b is a substrate modified with benzoic acid. The introduction of benzoic acid enhances the flexibility of the substrate and can withstand tens of thousands of bends.
[0047] like Fig.12 The water contact angle test diagram is shown. Fig.12 a and b are the water contact angles of the film prepared in the present invention and the film prepared based on NOA63 in Journal of Materials Chemistry C (2017): 10.1039, respectively. It can be seen that the water contact angle of Figure a is larger than that of Figure b, which proves that the film prepared in the present invention has good hydrophobicity and high humidity stability.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell, characterized in that: The method comprises the following preparation steps: Step 1: dissolving polyvinyl pyrrolidone in deionized water to form a mixture, stirring the mixture in air to form a precursor solution, and the prepared precursor solution can be spun; Step 2: Place the precursor solution into a syringe and a hemispherical droplet appears on the tip of the syringe; Step 3: Set the distance from the spinneret to the square collector, flow rate, and applied voltage range; Step 4: The hemispherical droplets are polarized under high voltage and spun in a square collector to form a nanofiber mesh; Step 5: Put anhydrous ethanol into a culture dish, heat it on a hot plate, place the nanofiber grid on top of the culture dish, and treat the nanofiber grid with anhydrous ethanol vapor to fuse the nodes between the fibers; Step 6: subjecting the nanofiber mesh to thermal evaporation treatment, evaporating metallic silver on the upper surface of the mesh and metallic copper on the lower surface; Step 7: Pre-treat the white glass: ultrasonically clean the white glass with deionized water, acetone, and isopropyl alcohol at room temperature, and then irradiate it with UV to make the white glass hydrophilic; Step 8: Spin deionized water over the pre-treated white glass surface to form a water film; Step 9: The nanofiber grid on the square collector is adhered to the white glass through the action of the water film. During the transfer process, the side of the nanofiber grid coated with metallic silver is adhered to the white glass; Step 10: doping benzoic acid into the polymethyl methacrylate solution to form a mixture, and heating and stirring the mixture to form a benzoic acid-modified polymethyl methacrylate solution; Apply the prepared solution dropwise on the white glass with the metal grid attached, apply it evenly with a scraper, then perform annealing and wait for it to dry; Step 11: Place the dried film in deionized water and let it stand, so that the film automatically falls off the white glass, and finally form a flexible transparent conductive electrode based on the copper-silver composite nanotube shell.
2. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: The concentration of the mixture formed in step 1 is 0.18-0.22 g / ml; Specifically, the mixture is stirred in air for 4-6 hours to form a precursor solution, and the prepared precursor solution can be spun in an air humidity range of 25%-32%.
3. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: In the step 3, the distance from the spinneret to the square collector, the flow rate, and the applied voltage range are set to 10-12 cm, 0.06-0.10 mm / min, and 7.5-8.5 kV, respectively.
4. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: In the step 4, the spinning time in the square collector is 100-130 s, and the coverage is 18%-22%.
5. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: In the step 5, 20-25 ml of anhydrous ethanol is put into a 35 ml culture dish, heated on a hot plate at 50° C., and the nanofiber grid is treated with anhydrous ethanol vapor for 2-3 minutes.
6. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: When the step six is to perform the thermal evaporation treatment, specifically, 50 nm of metallic silver is evaporated on the upper surface of the grid and 50 nm of metallic copper is evaporated on the lower surface, and the evaporation rate is 0.5-0.9 Å / s.
7. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: The step seven specifically involves ultrasonic cleaning the white glass for 15 minutes, followed by UV irradiation for 15 minutes.
8. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: In the step eight, 1-1.5 ml of deionized water is spread on the pretreated white glass surface, and spin coating is performed at a spin coating rate of 1500 rmp and a spin coating time of 30 s.
9. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: The step ten specifically comprises doping benzoic acid with a solid content of 7.5% into a 0.2 g / ml polymethyl methacrylate solution to form a mixture; and heating and stirring the mixture at a temperature of 80° C. and a stirring rate of 3000 rpm for 3 hours to form a benzoic acid-modified polymethyl methacrylate solution.
10. The method for preparing a flexible transparent conductive electrode based on a copper-silver composite nanotube shell according to claim 1, characterized in that: The step eleven specifically includes placing the dried film in deionized water and allowing it to stand for 60 seconds.
Citation Information
Patent Citations
Electroconductive laminate and process for production thereof
CN102574388A
Preparation method for transparent conductive metal network
CN103628028A
Transparent conductive electrode with concave structure and preparation method thereof
CN107910097A
Preparation method of flexible transparent conducting film with metal ordered grid
CN108962433A
One-dimensional metal nanowire embedded colorless polyimide film via potassium polyamate functionalization as a transparent electrode and it's fabrication by using potassium hydroxide
KR1020150095997A